Seal song - Davies, Brian, 1935- author (London : Allan Lane, 1978)
Describes in text and photographs the natural history of the harp seal, its physical characteristics, breeding, migratory and behavioral patterns, and natural environment. Also discusses the annual seal hunt in Canada.